2005
DOI: 10.1007/s10802-005-0933-0
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Adolescent Substance Use Among Sexually Abused Girls

Abstract: This study examined the link between childhood sexual abuse and adolescent substance use among girls, and evaluated depressive self-concept and behavioral under-control (BUC) as pathways to substance use for sexually abused girls. Participants (n = 150) were drawn from a longitudinal study of the impact of domestic violence on the lives of women and children. Structural equation modeling revealed that girls' childhood sexual abuse was associated prospectively with their later substance use. This relationship p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
3
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 50 publications
5
70
3
3
Order By: Relevance
“…For example, sexual abuse has been found to lead to more detrimental effects for girls later in life. Girls who were sexually abused were significantly more likely than boys to be arrested for a violent offense and to develop psychiatric disorders or substance abuse in adulthood (Bailey & McCloskey, 2005;Herrera & McCloskey, 2003). Additionally, although lack of emotional bonding with parents creates risk for boys, studies have found stronger correlations between lack of emotional bonding with parents and substance abuse for girls (Kakar, Friedemann, & Peck, 2002).…”
Section: Promoting Healthy Connectionsmentioning
confidence: 99%
“…For example, sexual abuse has been found to lead to more detrimental effects for girls later in life. Girls who were sexually abused were significantly more likely than boys to be arrested for a violent offense and to develop psychiatric disorders or substance abuse in adulthood (Bailey & McCloskey, 2005;Herrera & McCloskey, 2003). Additionally, although lack of emotional bonding with parents creates risk for boys, studies have found stronger correlations between lack of emotional bonding with parents and substance abuse for girls (Kakar, Friedemann, & Peck, 2002).…”
Section: Promoting Healthy Connectionsmentioning
confidence: 99%
“…Ova veza je bila stalna kada su faktori poput starosti, ostalih oblika zlostavljanja ( zičkog, izloženosti nasilju u porodici), depresije i agresije u detinjstvu, porodičnih prihoda i upotrebe psihoaktivnih supstanci od strane njihovih majki bili kontrolisani. 19 …”
unclassified
“…These two studies considered the mental health effects of maltreatment on adolescents. Experiences of maltreatment have been consistently reported in the literature to have myriad impacts on psychological functioning (e.g., Bailey & McCloskey, 2005;Lipschitz, Rasmusson, Anyan, Cromwell, & Southwick, 2000;Titus, Dennis, White, Scott, & Funk, 2003). Until recently, much of the extant research regarding maltreatment and trauma symptoms had been situated in the adult literature, comprising retrospective self-reports of childhood maltreatment incidents.…”
Section: Effects Of Maltreatment Experiencesmentioning
confidence: 99%
“…With regard to types of maltreatment experienced, girls are more likely to be sexually abused than boys (Clark, Lesnick, & Hegedus, 1997;Kilpatrick et al, 2000;Bailey & McCloskey, 2005). The DHHS reported that girls are as high as 4 times more likely to be sexually abused as boys (DHHS, 2001).…”
Section: Maltreatment and Aod Use In Girlsmentioning
confidence: 99%
See 1 more Smart Citation